2014
DOI: 10.1007/s00701-014-2306-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of incidentally discovered meningiomas

Abstract: Long-term tumour growth of incidentally detected asymptomatic meningiomas appeared to be much higher than expected. This information needs to be considered when discussing surgery, since the indication for surgery may be stronger than previously stated, especially for younger patients with tumours that can be reached at low risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 24 publications
0
51
0
2
Order By: Relevance
“…Yano et al reported no significant difference in initial size in diameter between growing and non-growing tumors indicating a p-value of 0.737 [21]. Robin etal and Jadid etal also found it insignificant [8,17]. In our meta analysis we found that tumor growth was associated with larger initial diameter (P= 0.01).…”
Section: Initial Tumor Size:-mentioning
confidence: 44%
See 4 more Smart Citations
“…Yano et al reported no significant difference in initial size in diameter between growing and non-growing tumors indicating a p-value of 0.737 [21]. Robin etal and Jadid etal also found it insignificant [8,17]. In our meta analysis we found that tumor growth was associated with larger initial diameter (P= 0.01).…”
Section: Initial Tumor Size:-mentioning
confidence: 44%
“…Nine of them could be statistically evaluated in our meta analysis [4,5,7,9,11,13,16,17,21], calcification was associated with significantly reduced risk of growth (P= 0.001). Furthermore Nakusa etal and Jadid etal [8,12] concluded the same results with different way of calculation. Only Hashiba et al reported that the presence of calcifications was more frequently observed in lesions that followed a linear growth pattern than in those following an exponential pattern (P= 0.05) [5] .…”
Section: Mri Findingsmentioning
confidence: 64%
See 3 more Smart Citations